Combined effects of physical illness and comorbid psychiatric disorder on risk of suicide in a national population study. (June 2014) - Qin, Ping; Hawton, Keith; Mortensen, Preben Bo; Webb, Roger
Abstract : Background: People with physical illness often have psychiatric disorder and this comorbidity may have a specific influence on their risk of suicide. Aims: To examine how physical illness and psychiatric comorbidity interact to influence risk of suicide, with particular focus on relative timing of onset of the two types of illness. Method: Based on the national population of Denmark, individual-level data were retrieved from five national registers on 27 262 suicide cases and 468 007 gender- and birth-date matched living controls. Data were analysed using conditional logistic regression. Results: Both suicides and controls with physical illness more often had comorbid psychiatric disorder than their physically healthy counterparts. Although both physical and psychiatric illnesses constituted significant risk factors for suicide, their relative timing of onset in individuals with comorbidity significantly differentiated the associated risk of suicide. While suicide risk was highly elevated when onsets of both physical and psychiatric illness occurred close in time to each other, regardless which came first, psychiatric comorbidity developed some time after onset of physical illness exacerbated the risk of suicide substantially. Conclusions: Suicide risk in physically ill people varies substantially by presence of psychiatric comorbidity, particularly the relative timing of onset of the two types of illness. Closer collaboration between general and mental health services should be an essential component of suicide prevention strategies.